Effects on the Cell Barrier Function of L-Met and DL-HMTBA Is Related to Metabolic Characteristics and m6A Modification - Zuo, Fangrui; Wei, Hongkui; Peng, Jian; Li, Shengqing; Zhou, Yuanfei (Frontiers in Nutrition, 2022)
Methionine (Met) is a substrate for protein synthesis and participates in many other biological events via its metabolism. We have previously demonstrated significant differences in the metabolism of L-methionine (L-Met) and its precursor DL-2-hydroxy-4-methylthiobutyric acid (DL-HMTBA) in IPEC-J2 cells. However, effects of metabolic differences on cell function remains unclear. This study showed that DL-HMTBA promoted Met transmethylation and improved the cell barrier function when the ratio of L-Met to DL-HMTBA was ≤ 40%:60%. This finding may be due to the decrease in the proportion of S-adenosylmethionine to S-adenosylhomocysteine and mRNA N6-methyladenosine (m6A) levels, which increase the mRNA stability and protein expression of tight junctions. To sum up, the effects of L-Met and DL-HMTBA on Met metabolism, especially transmethylation, suggest that DL-HMTBA has the potential to influence the intestinal barrier function of animals through epigenetic processes.